Effect of sarcoptic mange mite infestation on the growth and immunity in growing-finishing pigs - G L Keeler; D S Pollmann; Frank Blecha; A B Broce; E L Wooten (Kansas Agricultural Experiment Station Research Reports, 1983)
Twenty -eight pigs were used to evaluate the effect the sarcoptic mange mite infestation on growth and immunity of growing-finishing pigs. Although mange mite infestation did not affect gain, the white blood cell counts were increased (23.6 vs. 28.6) two weeks after the infestation, corresponding to the mite generation. Two weeks after the infestation lymphocytes were decreased (61.0 vs. 51. 3%) and neutrophils were increased (25.7 vs. 35.1%). It appears from these data that sarcoptic mange mite infestation may influence immune status of growing-finishing pigs.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Sarcoptic mange mite; Growth; Immunity; Growing-finishing pigs